Case Report: A complex case of neuropathy and temporomandibular disorders manifesting as otalgia - Shrivastava, Mayank; Soliman, Jacob; Ye, Liang (Frontiers in Oral Health, 2025)
Patients with temporomandibular disorders (TMDs) often present with otological symptoms as their primary complaint. Nervus intermedius neuropathy is a rare condition characterized by paroxysmal episodes of sharp, deep ear pain. The presence of overlapping symptoms of TMD and nervus intermedius neuropathy, associated with psychological comorbidities and sleep disturbances, poses significant diagnostic and management challenges for clinicians. Therefore, we report the case of a young female patient who presented to the orofacial pain clinic with debilitating ear pain affecting her quality of life. The patient responded partially to medications and conservative therapies. Adding psychosocial interventions along with botulinum toxin provided notable relief in refractory pain characteristics. In conclusion, although nervus intermedius neuropathy is uncommon in clinical practice, it may coexist with painful TMD and sleep and psychological problems. In such cases of refractory chronic pain, botulinum toxin injections may serve as a critical component for effective patient management.